Novelty and educational experience. Issue 1 (2nd January 2019) - Ingman, Benjamin C.
Abstract: Using the method of educational criticism and connoisseurship, I interviewed and observed 41 participants of adventure education (AE) programmes. Through these efforts, novelty was revealed as a central quality of the experience. In this work, this quality is characterised as it manifest in AE with an eye towards the educational value of novelty. The relationship of novelty to conceptions of educational experience is explored, and implications for schooling are offered.